Solution-focused brief counseling to improve student’s social-emotional skills and psychological well-being - Naraswari, Ida Ayu Made Diah; Dantes, Nyoman; Suarni, Ni Ketut; Gading, I Ketut; Suranata, Kadek (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Indonesian education has transformed along with the current situations. Through the implementation of guidance and counseling service, schools should facilitate students to develop various non-cognitive skills and ensure that student’s mental health can well-achieved. This study aims to examine the effectiveness of solution-focused brief counseling (SFBC) to improve student’s social-emotional skills and psychological well-being. Following the experimental pretest-posttest control group design procedure, 64 junior high school students were involved as research subjects. Instruments in this study used 71-item social-emotional skills questionnaire and 42-item psychological well-being scale. The experimental group will be following 9 sessions of counseling, while the control group will not involve in any intervention. Data analysis in this study was carried out using one-way ANOVA and MANOVA. Results of this study found that (1) SFBC is effective to improving student’s social-emotional skills, (2) SFBC is effective to improving student’s psychological well-being, and (3) SFBC is simultaneously effective to improve student’s social-emotional skills and psychological well-being. The findings of this study have implications for the use of SFBC model as an intervention method to improve student’s non-cognitive skills and psychological well-being.